Evaluation of Differential Sensitivity for Frequency, Intensity, and Duration in Individuals with Hypertension - Mahendran, Saranya; Prabhu, Prashanth (Annals of Otology and Neurotology, 2022)
Objective Hypertension is a condition in which the blood vessels have persistently raised pressure. The damage of the cochlea is due to the loss of sensitive hair cells in the inner ear or the damage to the eighth cranial nerve. When the cochlea is damaged, the functioning abilities such as coding, differentiation, and temporal processing abilities will be affected. Hence, there might be deficits in differential sensitivity in individuals with hypertension. The aim of this article was to study the effect of hypertension on differential sensitivity as there is limited literature in this area.Method Thirty participants were included in the study and classified into two groups: group I as individuals with hypertension and group II as individuals with normal blood pressure in the age range of 25 to 45 years. Psychophysical tests like frequency, intensity, and time discrimination tests were performed using the maximum likelihood procedure (MLP) toolbox, which implements a maximum likelihood procedure for threshold estimation in MATLAB.Results In all the three test conditions, the scores were significantly poorer in individuals with hypertension compared with individuals of the normal at all the frequencies such as 500 Hz, 1,000 Hz, 2,000 Hz, and 4,000 Hz.Conclusion This could be because of reduced frequency selectivity and poor temporal coding as well as due to difficulty responding to rapid change in the envelope of sound over time because of cochlear and neural damage in individuals with hypertension.
Keywords: hypertension; differential sensitivity; blood supply; temporal coding